Active energy ray-curable conductive paste and wiring board
The combination of flake-like electrical particles and specific monomer acrylates in the conductive paste addresses issues of reduced permeability and adhesion, achieving stable conductivity and durability in active energy ray-curing pastes.
Patent Information
- Application Number
- JP2023119688
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-24
- Publication Date
- 2025-02-05
Smart Images

Figure 2025016895000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an active energy ray-curable conductive paste and a wiring board using the same. [Background technology]
[0002] 2. Description of the Related Art Conductive paste is known as a material used for forming signal wiring on a printed wiring board. Among conductive pastes, active energy ray curable conductive pastes, unlike heat curable conductive pastes, do not require a high temperature curing process and are therefore used in wiring board applications using plastic films such as polyethylene terephthalate films as substrates that are easily damaged at high temperatures. Active energy ray curable conductive pastes, which can be cured / dried using active energy rays such as ultraviolet rays and electron beams, are industrially useful as they require less heating.
[0003] The conductive powder used in the conductive paste may be a metal such as gold, platinum, silver, or palladium that does not oxidize in air, but silver or a silver compound is generally used. In addition, flake-shaped conductive particles may be used to make it easier to obtain electrical continuity by contact between the particles of the conductive powder. For example, Patent Document 1 discloses an active energy ray-curable conductive paste that contains silver particles, urethane acrylate, a nitrogen-containing monofunctional monomer, and a polymerization initiator.
[0004] However, when flake-shaped conductive fine particles are used to improve conductivity, there is a problem that the transmittance of ultraviolet rays, which are active energy rays, decreases, and the curing property of the signal wiring made of the conductive paste decreases. Furthermore, conventional active energy ray-curable conductive pastes have a problem that they undergo a large volume shrinkage due to curing, and have low adhesion to the substrate. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2007-119682 A Summary of the Invention [Problem to be solved by the invention]
[0006] The present invention aims to provide an active energy ray-curable conductive paste and a wiring board that have excellent adhesion to glass as well as ITO (indium tin oxide) vapor-deposited substrates, and further have good durability, and that have both electrical conductivity and curability. [Means for solving the problem]
[0007] The present invention relates to an active energy ray-curable conductive paste that contains flaky conductive fine particles having a thickness of 0.5 to 5 μm and an aspect ratio of 1 to 20, an amine-modified polyfunctional oligomer (A), a monofunctional (meth)acrylate having an alicyclic hydrocarbon group (B), and a polymerization initiator, and that contains 50 to 95 mass% of the flaky conductive fine particles based on the total mass of the paste.
[0008] The present invention also relates to the active energy ray-curable conductive paste, wherein the monofunctional (meth)acrylate (B) having an alicyclic hydrocarbon group contains a monofunctional (meth)acrylate having a polycyclic alicyclic hydrocarbon group.
[0009] The present invention also relates to the active energy ray-curable conductive paste, wherein the mass ratio ((A):(B)) of the amine-modified polyfunctional oligomer (A) to the monofunctional (meth)acrylate having an alicyclic hydrocarbon group (B) is 95:5 to 5:95.
[0010] The present invention also relates to the active energy ray-curable conductive paste, wherein the amine-modified polyfunctional oligomer (A) has a hydroxyl group and a weight average molecular weight of 500-2,000.
[0011] The present invention also relates to the active energy ray-curable conductive paste, which further contains a monomer (C) having at least one structure selected from a cycloolefin structure, a trimethylolpropane-derived structure, an epoxy-derived structure, a pentaerythritol-derived structure, and a glycerin-derived structure (excluding the oligomer (A) and the monofunctional (meth)acrylate (B)).
[0012] The present invention also relates to the active energy ray-curable conductive paste, which is for screen printing.
[0013] The present invention also relates to a wiring board having a conductive layer formed on a substrate from the active energy ray-curable conductive paste.
[0014] The present invention also relates to an electronic device comprising the above wiring board. Effect of the Invention
[0015] According to the present invention described above, it is possible to provide an active energy ray-curable conductive paste and a wiring board which have good adhesion to a substrate, excellent durability, and both electrical conductivity and curability.
[0016] In particular, it is possible to provide an active energy ray-curable conductive paste that can provide good adhesion to ITO (indium tin oxide) vapor-deposited substrates as well as glass. [Brief description of the drawings]
[0017] [Figure 1] 1 is a schematic cross-sectional view showing the configuration of a wiring board to which the active energy ray-curable conductive paste of the present invention is applied. [Diagram 2] 1 is a schematic cross-sectional view showing the configuration of a touch panel to which the active energy ray-curable conductive paste of the present invention is applied. [Diagram 3] FIG. 1 is a schematic cross-sectional view showing the configuration of an organic thin-film solar cell to which the active energy ray-curable conductive paste of the present invention is applied. [Figure 4]1 is a schematic cross-sectional view showing the configuration of a photosensitized solar cell to which the active energy ray-curable conductive paste of the present invention is applied. [Diagram 5] 1 is a schematic cross-sectional view showing the configuration of a non-contact ID to which the active energy ray-curable conductive paste of the present invention is applied. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] The following describes the embodiments of the present invention in detail. However, the following description of the requirements and other aspects is a representative example of an embodiment of the present invention, and the present invention is not limited to these details as long as it does not exceed the spirit of the invention.
[0019] The active energy ray-curable conductive paste of the present invention contains flaky conductive fine particles having a thickness of 0.5 to 5 μm and an aspect ratio of 1 to 20, an amine-modified polyfunctional oligomer (A), a monofunctional (meth)acrylate having an alicyclic hydrocarbon group (B), and a polymerization initiator. The active energy ray curable conductive paste is cured by irradiating a coating layer formed on a substrate by printing (including coating or spreading) with active energy rays, thereby forming a conductive layer. When the conductive layer is a signal wiring, the signal wiring is preferably used for wiring board applications.
[0020] Examples of active energy rays include ultraviolet rays, electron beams, and visible light rays, and from the viewpoint of curing properties, ultraviolet rays are preferred.
[0021] The active energy ray curable conductive paste contains an amine-modified polyfunctional oligomer (A) and a monofunctional (meth)acrylate having an alicyclic hydrocarbon group (B), which suppresses the curing shrinkage of the coating layer when cured with active energy rays, and improves adhesion to the substrate due to the presence of nitrogen atoms with high electronegativity and promotion of wetting due to a decrease in surface free energy. Furthermore, since a rigid skeleton is introduced into the coating layer and it has high affinity with the surface of the conductive fine particles, the adhesion and conductivity are less likely to change due to environmental changes such as temperature shock, and the stability of these is improved. In addition, by using flaky conductive fine particles with a thickness of 0.5 to 5 μm and an aspect ratio of 1 to 20, when irradiated with active energy rays, ultraviolet light reflects off the gaps between the overlapping flaky conductive fine particles in the coating layer and penetrates from the upper layer to the lower layer, thereby achieving both curability and conductivity.
[0022] <Flake-shaped conductive fine particles> The flaky conductive fine particles in the present invention have a thickness of 0.5-5 μm and an aspect ratio of 1-20. By satisfying a thickness of 0.5 to 5 μm and an aspect ratio of 1 to 20, the flaky conductive fine particles in the coating layer can suppress the reflection of active energy rays such as ultraviolet rays and can easily capture active energy rays into the gaps between the flaky conductive fine particles. This further improves the curability. The aspect ratio can be calculated by [average major axis (μm)] / [average thickness (μm)]. The average major axis (μm) is an average value obtained by directly observing the major axis and thickness of about 30 particles in an image at a magnification (about 2000 times) using a scanning electron microscope. The aspect ratio is preferably 2 to 17, and more preferably 3 to 15.
[0023] The thickness of the flake-shaped conductive fine particles can be determined by preparing an active energy ray-curable conductive paste, printing a conductive layer, and averaging the thicknesses of approximately 30 particles from a magnified image of the cross section of the conductive layer taken with a scanning electron microscope (magnification of approximately 2000 times). Another method involves preparing a sample by hardening a mixture of flake-shaped conductive fine particles and a commercially available epoxy resin, and using a scanning electron microscope to measure the thickness of the cross section of the sample in the same manner as above.
[0024] Examples of the material of the flake-shaped conductive fine particles include metals such as gold, silver, copper, amorphous copper, nickel, chromium, palladium, rhodium, ruthenium, indium, silicon, aluminum, tungsten, molybdenum, and platinum, as well as alloys thereof, silver oxide, and metal oxides such as indium oxide, antimony oxide, zinc oxide, tin oxide, antimony-doped tin oxide, ruthenium oxide, and indium-tin composite oxide (ITO), as well as carbon black and graphite. The material may be, for example, a composite metal such as silver-plated copper powder. It may also be a coated particle in which a non-conductive particle is coated with the metal, metal oxide, or the like. Among these, metal fine particles or metal oxide fine particles are preferable from the viewpoint of conductivity, and silver fine particles are more preferable.
[0025] The flake-shaped conductive fine particles may be used alone or in combination with non-flake-shaped conductive fine particles, such as spherical, dendritic, and acicular. The average particle size of the flaky conductive fine particles is preferably from 3 to 15 μm, and more preferably from 5 to 10 μm. The active energy ray-curable conductive paste contains 50 to 95 mass % of flake-shaped conductive fine particles in the total mass, and more preferably 65 to 95 mass %.
[0026] The amount of the flaky conductive fine particles is preferably 50:50 to 95:5, more preferably 70:30 to 90:10, where X is the content of the flaky conductive fine particles and Y is the content of the active energy ray curing component. By blending an appropriate amount of the flaky conductive fine particles, it is possible to achieve both electrical conductivity and printability. The active energy ray curing component includes an amine-modified multifunctional oligomer (A) and a compound having an ethylenically unsaturated double bond, such as a monofunctional (meth)acrylate (B) having an alicyclic hydrocarbon group, and further includes compounds other than the amine-modified multifunctional oligomer (A) and the monofunctional (meth)acrylate (B) having an alicyclic hydrocarbon group, as long as the compound has an ethylenically unsaturated double bond.
[0027] In this specification, "polyfunctional" refers to having multiple ethylenically unsaturated double bonds in one molecule, "monofunctional" refers to having one ethylenically unsaturated double bond in one molecule, and the number of functional groups refers to the number of ethylenically unsaturated double bonds in one molecule.
[0028] The ethylenically unsaturated double bond refers to a group that undergoes a polymerization reaction with active energy rays, and suitable examples thereof include an acrylic group, a methacrylic group, etc. In this specification, "(meth)acrylate" refers to both acrylate and methacrylate, and "(meth)acrylic" refers to both acrylic and methacrylic.
[0029] <Amine-modified multifunctional oligomer (A)> Amine-modified means having a substituted amino group, and the amine-modified polyfunctional oligomer (A) is an oligomer having a secondary or tertiary amine structure and a plurality of ethylenically unsaturated double bonds in the same molecule. The amine-modified polyfunctional oligomer (A) preferably has a hydroxyl group, preferably has 2 to 4 ethylenically unsaturated double bonds, and preferably has a weight average molecular weight of 500 to 2000. The oligomer (A) preferably has at least one structure selected from a polyester acrylate structure, a urethane acrylate structure, and an epoxy acrylate structure. It is more preferable that the oligomer (A) contains a polyester acrylate structure. The amine-modified polyfunctional oligomer (A) preferably has a tertiary amino group. By including the amine-modified polyfunctional oligomer (A), the active energy ray-curable conductive paste has improved adhesion to the substrate and curability, particularly to a substrate having a transparent electrode made of a metal oxide such as ITO.
[0030] The amine-modified polyfunctional oligomer (A) can be obtained by an addition reaction between a polyfunctional acrylate such as polyester acrylate, urethane acrylate, or epoxy acrylate and an amine compound. For example, the following production method can be mentioned. A tetrafunctional (meth)acrylate oligomer having a tertiary amino group can be synthesized by addition reaction of a multifunctional acrylate, trifunctional (meth)acrylate (2 moles), with an amine compound, alkanolamine (1 mole). Specifically, the addition reaction is such that one acrylate group of a trifunctional (meth)acrylate is added to a primary amino group of an alkanolamine to form a multifunctional oligomer having a secondary amino group. Furthermore, if an acrylate group of a trifunctional (meth)acrylate and the secondary amino group undergo an addition reaction, a multifunctional oligomer having a tertiary amino group is formed. The number of functional groups and the molecular weight of the amine-modified multifunctional oligomer (A) can be adjusted by controlling the type of multifunctional acrylate and its reaction ratio.
[0031] <Polyester acrylate> Examples of the trifunctional (meth)acrylate as the polyester acrylate include trimethylolpropane tri(meth)acrylate, ethylene oxide-added trimethylolpropane tri(meth)acrylate, propylene oxide-added trimethylolpropane tri(meth)acrylate, glycerin tri(meth)acrylate, ethylene oxide-added glycerin tri(meth)acrylate, propylene oxide-added glycerin tri(meth)acrylate, pentaerythritol tri(meth)acrylate, ethylene oxide-modified pentaerythritol tri(meth)acrylate, and propylene oxide-modified pentaerythritol tri(meth)acrylate. etc. are preferred. In addition, trifunctional (meth)acrylate monomers having a structure in which ethylene oxide, propylene oxide or other alkylene oxides are added are preferred.
[0032] Furthermore, the polyfunctional acrylate as the polyester acrylate may be a tetrafunctional to hexafunctional acrylate, and examples of the hexafunctional acrylate include dipentaerythritol hexa(meth)acrylate or its ethylene oxide or propylene oxide adduct, examples of the pentafunctional acrylate include dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, and the like, and examples of the tetrafunctional acrylate include diglycerol EO-modified (meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, and pentaerythritol tetra(meth)acrylate.
[0033] Furthermore, the polyfunctional acrylate as the polyester acrylate may be a bifunctional acrylate, and examples of the bifunctional acrylate include ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, butylene glycol di(meth)acrylate, pentyl glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, Preferred examples of the tert-butyl ether di(meth)acrylate include tert-butyl ether di(meth)acrylate, hydroxypivalyl hydroxypivalate di(meth)acrylate (commonly known as manda), hydroxypivalyl hydroxypivalate dicaprolactonate di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,2-hexanediol di(meth)acrylate, 1,5-hexanediol di(meth)acrylate, tricyclodecane dimethylol dicaprolactonate di(meth)acrylate, tricyclodecane methanol di(meth)acrylate, bisphenol A tetraethylene oxide adduct di(meth)acrylate, and bisphenol F tetraethylene oxide adduct di(meth)acrylate.
[0034] <Urethane acrylate> Examples of hexafunctional urethane acrylates include pentaerythritol tri(meth)acrylate hexamethylene diisocyanate adducts, pentaerythritol tri(meth)acrylate, toluene diisocyanate adducts, pentaerythritol tri(meth)acrylate, and isophorone diisocyanate adducts. Examples of tetrafunctional urethane acrylates include glycerin di(meth)acrylate hexamethylene diisocyanate adducts and trimethylolpropane di(meth)acrylate isophorone diisocyanate adducts. Examples of trifunctional urethane acrylates include ethoxylated isocyanuric acid tri(meth)acrylate and ε-caprolactone-modified tris-(2-meth)acryloxyethyl)isocyanurate. Examples of bifunctional urethane acrylates include hydroxyethyl (meth)acrylate hexamethylene diisocyanate adducts and hydroxybutyl (meth)acrylate isophorone diisocyanate adducts.
[0035] <Epoxy acrylate> Examples of epoxy acrylates include the EBECRYL series manufactured by Daicel-Allnex Co., Ltd. Examples of tetrafunctional epoxy acrylates include EBECRYL860 (epoxidized soybean oil acrylate), examples of trifunctional epoxy acrylates include EBECRYL3603 (novolac epoxy acrylate), and examples of difunctional epoxy acrylates include EBECRYL600 bisphenol A type epoxy acrylate.
[0036] <Amine compounds> The amine compound is preferably an alkanolamine, and suitable examples thereof include methanolamine, ethanolamine, propanolamine, butanolamine, diethanolamine, etc. By using an alkanolamine, a hydroxyl group can be imparted to the amine-modified polyfunctional oligomer (A).
[0037] As the amine compound other than the alkanolamine, alkylamine, aniline, and other amine compounds having a primary or secondary amino group are preferable.
[0038] The amine-modified polyfunctional oligomer (A) can be used alone or in combination with two or more kinds, and is preferably contained in an amount of 0.1 to 10 mass % and more preferably 1 to 5 mass % based on the total mass of the active energy ray-curable conductive paste.
[0039] <Monofunctional (meth)acrylate having an alicyclic hydrocarbon group (B)> The monofunctional (meth)acrylate (B) having an alicyclic hydrocarbon group is preferably a monofunctional (meth)acrylate having a polycyclic alicyclic hydrocarbon group. Examples of the monofunctional (meth)acrylate having a monocyclic alicyclic hydrocarbon group include cyclohexyl acrylate, cyclohexyl methacrylate, 3,3,5-trimethylcyclohexyl acrylate, 3,3,5-trimethylcyclohexyl methacrylate, and 1,4-cyclohexanedimethanol monoacrylate. Examples of the monofunctional (meth)acrylate having a polycyclic alicyclic hydrocarbon group include isobornyl acrylate. Examples of the methacrylate include isobornyl methacrylate, dicyclopentenyl acrylate, dicyclopentenyl methacrylate, dicyclopentenyloxyethyl acrylate, dicyclopentenyloxyethyl methacrylate, dicyclopentanyl acrylate, dicyclopentanyl methacrylate, adamantyl-1-acrylate, adamantyl-1-methacrylate, 2-methyladamantyl-2-acrylate, 2-methyladamantyl-2-methacrylate, 2-ethyladamantyl-2-acrylate, and 2-ethyladamantyl-2-methacrylate. Among the above, isobornyl acrylate and isobornyl methacrylate are particularly preferred.
[0040] By including both the amine-modified polyfunctional oligomer (A) and the monofunctional (meth)acrylate having an alicyclic hydrocarbon group (B), the cured coating of the active energy ray-curable conductive paste has good adhesion to the substrate. In particular, it is more preferable that the monofunctional (meth)acrylate having an alicyclic hydrocarbon group (B) is a monofunctional (meth)acrylate having a polycyclic alicyclic hydrocarbon group, since the polycyclic alicyclic hydrocarbon group exerts an anchoring effect (penetrating into the fine irregularities of the substrate to improve adhesion). The mass ratio ((A) / (B)) of (A) and (B) is preferably 95 / 5 to 5 / 95, more preferably 90 / 10 to 10 / 90, and even more preferably 40 / 60 to 10 / 90. The total amount of the amine-modified polyfunctional oligomer (A) and the monofunctional (meth)acrylate having an alicyclic hydrocarbon group (B) in the active energy ray-curable conductive paste is preferably 1 to 30 mass%, more preferably 3 to 20 mass%, and even more preferably 5 to 10 mass%. By including an appropriate amount of both monomers, both adhesion and curability can be more highly achieved.
[0041] <Polymerization initiator> Examples of the polymerization initiator include benzoin-based initiators such as benzoin, benzoin methyl ether, benzoin isopropyl ether, and α-acrylbenzoin, 2,2-dimethoxy-1,2-diphenylethan-1-one (Irgacure 651, manufactured by BASF), 1-hydroxycyclohexylphenylketone (Irgacure 184, manufactured by BASF), 2-hydroxy-2-methyl-1-phenylpropan-1-one (Darocure 1173, manufactured by BASF), 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy, and the like. -2-Methyl-1-propan-1-one (Irgacure 2959: BASF), 2-methyl-1[4-(methylthio)phenyl]-2-morpholinopropan-1-one (Irgacure 907: BASF), 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butanone-1 (Irgacure 369: BASF), bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide (Irgacure 819: BASF), 2,4,6-trimethylbenzoyl-diphenyl-phosphine thioxanthone (Darocure TPO: BASF), 2-hydroxy-1-{4-[4-(2-hydroxy-2-methylpropyl)-benzyl]-phenyl}-2-methyl-propan-1-one (Irgacure 127: BASF), 2-dimethylamino-2-(4-methyl-benzyl)-1-(4-morpholin-4-yl-phenyl)-butan-1-one (Irgacure 379: BASF), 2,4-diethylthioxanthone (Kayacure DETX-S: Nippon Kayaku), 2-chlorothioxanthone (Kayacure -CTX: manufactured by Nippon Kayaku Co., Ltd.), benzophenone (Kayacure BP-100: manufactured by Nippon Kayaku Co., Ltd.), [4-(methylphenylthio)phenyl]phenylmethane (Kayacure BMS: manufactured by Nippon Kayaku Co., Ltd.), ethyl anthraquinone (Kayacure 2-EAQ: manufactured by Nippon Kayaku Co., Ltd.), Esacure KIP100 (manufactured by SiberHegner Co., Ltd.), diethoxyacetophenone, bis(2,6-dimethoxybenzoyl)-2,4,4-trimethyl-pentylphosphine oxide (BAPO1: manufactured by BASF), and BTTB (manufactured by Nippon Oil & Fats Co., Ltd.).
[0042] Among these, 2-dimethylamino-2-(4-methyl-benzyl)-1-(4-morpholin-4-yl-phenyl)-butan-1-one (Irgacure 379: manufactured by BASF), 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butanone-1 (Irgacure 369: manufactured by BASF), 2,4-diethylthioxanthone (Kayacure DETX-S: manufactured by Nippon Kayaku Co., Ltd.), and 2,4,6-trimethylbenzoyl-diphenyl-phosphine oxide (Darocur TPO: manufactured by BASF) are more preferred in terms of improving curability and adhesion.
[0043] The polymerization initiator may be used alone or in combination of two or more kinds.
[0044] The active energy ray-curable conductive paste preferably contains 0.1 to 10 mass %, more preferably 0.3 to 3 mass % of the polymerization initiator. When an appropriate amount of the polymerization initiator is contained, it is easy to achieve both curability and adhesion.
[0045] <Monomer (C)> The active energy ray curable conductive paste preferably further contains a monomer (C). The monomer (C) is a compound having an ethylenically unsaturated double bond other than the amine-modified polyfunctional oligomer (A) and the monofunctional (meth)acrylate (B) having an alicyclic hydrocarbon group, and refers to a monomer having at least one structure selected from a cycloolefin structure, a trimethylolpropane-derived structure, an epoxy-derived structure, a pentaerythritol-derived structure, and a glycerin-derived structure. By having this structure, it is possible to suppress the shrinkage of the cured coating after active energy ray curing, and it is excellent in curability, printing viscosity, adhesion, etc. Among the above, a monomer having an epoxy-derived structure is particularly preferable. The molecular weight of the monomer (C) is preferably 100 to 500. The number of functional groups of the monomer (C) is preferably 1 to 4, and more preferably 2 to 3.
[0046] The ratio of the total mass of the monomer (C) to the total mass ((A)+(B)) of the amine-modified polyfunctional oligomer (A) and the monofunctional (meth)acrylate (B) having an alicyclic hydrocarbon group is preferably ((A)+(B)):(C)=50:50 to 100:0, and more preferably 50:50 to 95:5.
[0047] The monomer (C) may be used alone or in combination with two or more kinds, and is preferably contained in an amount of 1 to 10 mass %, more preferably 2 to 5 mass %, based on the total mass of the active energy ray-curable conductive paste.
[0048] Preferred examples of the monomer (C) having a cycloolefin-derived structure include 1,4-cyclohexanedimethanol mono(meth)acrylate, 1,4-cyclohexanedimethanol di(meth)acrylate, tricyclodecanedimethyloldicaprolactonate di(meth)acrylate, and tricyclodecanemethanol di(meth)acrylate.
[0049] Examples of the monomer (C) having a trimethylolpropane-derived structure include preferably trimethylolpropane tri(meth)acrylate, trimethylolpropane tricaprolactonate tri(meth)acrylate, trimethylolethane tri(meth)acrylate, trimethylolhexane tri(meth)acrylate, trimethyloloctane tri(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, ditrimethylolpropane tetracaprolactonate tetra(meth)acrylate, ditrimethylolethane tetra(meth)acrylate, ditrimethylolbutane tetra(meth)acrylate, ditrimethylolhexane tetra(meth)acrylate, and ditrimethyloloctane tetra(meth)acrylate.
[0050] Examples of the monomer (C) having an epoxy-derived structure include tetrafunctional epoxy acrylates such as epoxidized soybean oil acrylate, trifunctional epoxy acrylates such as novolac epoxy acrylate, and difunctional epoxy acrylates such as bisphenol A type epoxy acrylate.
[0051] Preferred examples of the monomer (C) having a pentaerythritol-derived structure include pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, pentaerythritol tetracaprolactonate tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, tripentaerythritol hexa(meth)acrylate, tripentaerythritol hepta(meth)acrylate, tripentaerythritol octa(meth)acrylate, and pentaerythritol polyalkylene oxide hepta(meth)acrylate.
[0052] Preferred examples of the monomer (C) having a structure derived from glycerin include glycerin tri(meth)acrylate and diglycerin tetra(meth)acrylate.
[0053] <Other monomers> The active energy ray-curable conductive paste may contain other monomers than those mentioned above as long as the effects of the paste are not impaired. Examples of such monomers are shown below.
[0054] The monofunctional monomer is preferably a (meth)acrylate having an alkyl chain with 1 to 18 carbon atoms, such as methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, hexyl (meth)acrylate, octyl (meth)acrylate, dodecyl (meth)acrylate, and stearyl (meth)acrylate. Other monofunctional monomers include (meth)acrylates having an aromatic ring, such as benzyl (meth)acrylate, butylphenol (meth)acrylate, octylphenol (meth)acrylate, nonylphenol (meth)acrylate, and dodecylphenol (meth)acrylate.
[0055] Examples of bifunctional monomers include ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, butylene glycol di(meth)acrylate, pentyl glycol di(meth)acrylate, and neopentyl Examples of such di(meth)acrylates include glycol di(meth)acrylate, hydroxypivalyl hydroxypivalate di(meth)acrylate (commonly known as Manda), hydroxypivalyl hydroxypivalate dicaprolactonate di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,2-hexanediol di(meth)acrylate, 1,5-hexanediol di(meth)acrylate, bisphenol A tetraethylene oxide adduct di(meth)acrylate, and bisphenol F tetraethylene oxide adduct di(meth)acrylate.
[0056] The active energy ray-curable conductive paste may contain the following components as long as the problem can be solved: binder resin, polymerization inhibitor, plasticizer, lubricant, organic solvent, dispersant, leveling agent, defoamer, antioxidant, and sulfurization inhibitor.
[0057] It is preferable to contain a polymerization inhibitor from the viewpoint of preventing gelation (preventing excessive reaction) and achieving uniform curing. Examples of such compounds include 4-teat-butylcatechol, hydroquinone, t Examples of the conductive agent include but are not limited to N-nitroso-N-phenylhydroxylamine ammonium salt, N-nitrosophenylhydroxylamine aluminum salt, and the like. Among these, N-nitrosophenylhydroxylamine aluminum salt is preferably used. The content of the conductive agent is preferably 0.01 to 0.1 mass % based on the total mass of the active energy ray-curable conductive paste.
[0058] <Organic solvent> The organic solvent is preferably used in an amount of 0 to 10% by mass based on the total mass of the active energy ray-curable conductive paste. Examples of the organic solvent include ketones, aromatic solvents, alcohols, cellosolves, and glycerols. Preferred are ethanol ethers, esters, aliphatic solvents, petroleum solvents, and the like. Examples of ketones include acetone, methyl ethyl ketone, methyl isobutyl ketone, 3-pentanone, 2-heptanone, diisobutyl ketone, isophorone, cyclohexanone, gamma-butyl lactone, etc. Examples of aromatic solvents include benzene, toluene, xylene, ethylbenzene, diethylbenzene, alkylbenzenes having an alkyl chain with 5 to 20 carbon atoms, etc. Examples of the alcohol include methanol, ethanol, normal propanol, isopropanol, normal butanol, isobutanol, neopentyl butanol, hexanol, octanol, ethylene glycol, propylene glycol, and benzyl alcohol. Examples of cellosolve include methyl cellosolve, ethyl cellosolve, butyl cellosolve, and hexyl cellosolve. Examples of glycol ethers include ethylene glycol monoethyl ether, ethylene glycol monoisopropyl ether, ethylene glycol monobutyl ether, diethylene glycol monoethyl ether, diethylene glycol mono-n-butyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol mono-n-propyl ether, propylene glycol mono-n-butyl ether, dipropylene glycol monomethyl ether, and dipropylene glycol mono-n-propyl ether. Examples of esters include ethyl acetate, butyl acetate, and diethylene glycol monoethyl ether. Examples of the acetates include diethylene glycol monobutyl ether acetate, and propylene glycol monomethyl ether acetate. Examples of the aliphatic solvent include n-heptane, n-hexane, cyclohexane, methylcyclohexane, and ethylcyclohexane. Examples of the petroleum-based solvent include aroma-free solvents and heavy aroma solvents.
[0059] <Other resins> The active energy ray curable conductive paste of the present invention may contain a resin other than the above (A), (B) or (C) within a range that does not impair its effects. The resin is preferably a resin that does not contain an ethylenically unsaturated double bond and has a number average molecular weight of 1,000 to 100,000. Examples of the resin include polyurethane resin, polyester resin, alkyd resin, butyral resin, acetal resin, polyamide resin, acrylic resin, styrene-acrylic resin, styrene resin, nitrocellulose resin, benzyl cellulose resin, styrene-maleic anhydride resin, polybutadiene resin, polyvinyl chloride resin, polyvinyl acetate resin, fluororesin, silicone resin, epoxy resin, phenol resin, maleic acid resin, urea resin, melamine resin, benzoguanamine resin, ketone resin, rosin, rosin ester, chlorinated polyolefin, modified chlorinated polyolefin, chlorinated polyurethane, etc., and the active energy ray curable conductive paste is preferably contained in an amount of less than 40 mass%, more preferably 0 to 5 mass%, based on the total mass of the active energy ray curable conductive paste.
[0060] <Method of manufacturing active energy ray curable conductive paste> An example of a method for producing an active energy ray curable conductive paste will be described. An amine-modified polyfunctional oligomer (A), a monofunctional (meth)acrylate having an alicyclic hydrocarbon group (B), a monomer having at least one structure selected from a cycloolefin structure, a trimethylolpropane-derived structure, an epoxy-derived structure, a pentaerythritol-derived structure, and a glycerin-derived structure (C), a polymerization initiator, and additives are put into a kneader and stirred and kneaded. It is preferable to then put in flake-shaped conductive fine particles and further stir or knead to produce the paste. When adjusting the viscosity of the active energy ray curable conductive paste, it is preferable to appropriately put in a monofunctional (meth)acrylate having an alicyclic hydrocarbon group (B) or a low-viscosity monomer, an organic solvent, or the like. It is also preferable to put in the flake-shaped conductive fine particles after dispersing them with other blending components in advance.
[0061] Examples of the kneading machine include a disper, a ball mill, a sand mill, a gamma mill, and a three-roll mill, and among these, the use of a three-roll mill is preferred.
[0062] The obtained active energy ray-curable conductive paste is printed on a substrate to form a coating layer, and then irradiated with active energy rays to form a conductive layer. Examples of the printing method include screen printing, inkjet printing, gravure offset printing, etc., and screen printing is preferred.
[0063] <Conductive layer formed from active energy ray curable conductive paste> A specific example of the conductive layer is a method of forming a desired pattern by rotary screen printing using a cylindrical screen plate, followed by curing by irradiation with active energy rays, or a method of forming a desired pattern by flat screen printing. In the latter case, the active energy rays can be irradiated at any time after the coating layer is formed. The thickness of the conductive layer is preferably 2 to 20 μm, more preferably 5 to 15 μm.
[0064] The active energy ray curable conductive paste of the present invention is cured by passing through an ultraviolet ray irradiation device such as a high pressure mercury lamp, a metal halide lamp and a conveyor. In order to cure sufficiently, the conveyor speed must be 3m / min or less under one air-cooled metal halide lamp of 120w / cm. The conveyor speed can be increased by using a lamp with a higher output and a good irradiation dose (500 mJ / cm2 or more), or by increasing the number of lamps.
[0065] <Base material> The substrate is preferably, for example, a paper substrate, a plastic substrate, or a composite substrate thereof. The thickness of the substrate is preferably about 50 to 200 μm. Examples of paper substrates include fine paper, synthetic paper, coated paper, and processed paper. Examples of processed paper include impregnated paper, waterproof paper, insulating paper, and stretchable paper. Among these, in order to obtain a stable resistance value, the use of coated paper or processed paper further improves the conductivity. Note that the conductivity of coated paper improves in proportion to the smoothness of the paper.
[0066] Examples of the plastic substrate include polyethylene terephthalate, polyester, polyethylene, polypropylene, cellophane, vinyl chloride, vinylidene chloride, polystyrene, vinyl alcohol, ethylene-vinyl alcohol, nylon, polyimide, polycarbonate, and glass. The substrate is preferably in the form of a sheet or plate. In addition, it is preferable that the substrate is surface-treated to enhance adhesion with the conductive layer. The surface treatment may be a dry treatment or a wet treatment. Examples of the dry treatment may include a corona treatment, a plasma treatment, and a frame treatment. Examples of the wet treatment may include an anchor coat agent.
[0067] The substrate preferably has a functional layer such as a deposition layer or coating layer on the surface. Examples of the deposition layer include ITO and silicon oxide. The coating layer is preferably a conductive layer containing a conductive material such as silver nanowires, carbon nanotubes, or a composite of poly(3,4-ethylenedioxythiophene) and polystyrene sulfonic acid (PEDOT-PSS). It is nice.
[0068] <Wiring board with conductive layer> The wiring board of the present invention comprises a substrate and a conductive layer formed from an active energy ray-curable conductive paste. The conductive layer functions as a signal wiring and can conduct electricity as an electric signal such as a wiring circuit, a ground wiring, an antenna wiring, etc. The wiring board is preferably used as, for example, a printed circuit board or a flexible printed circuit board.
[0069] <Electronic device having a wiring board> The electronic device of the present invention includes a wiring board. Examples of the electronic device include a solar cell, a touch panel, and a non-contact ID.
[0070] Fig. 1 shows an example of a basic configuration using a wiring board. For example, on three substrates such as polyester film, the active energy ray curable conductive paste of the present invention is patterned into two signal wiring patterns by screen printing or the like, and then irradiated with active energy rays, after which one insulating layer (protective layer) is printed on the required portion.
[0071] Figure 2 shows an example of the configuration of a touch panel. Signals obtained from the ITO of the transparent conductive (ITO) film X 7a and the transparent conductive (ITO) film Y 7b, which detect signals of the X-axis and Y-axis on the display 8, are collected by the active energy ray curable conductive paste (6a, 6b) of the present invention printed around the periphery. The display 8, the transparent conductive (ITO) film X 7a, the transparent conductive (ITO) film Y 7b, and the cover glass 4 are attached together by a transparent adhesive sheet 5OCA.
[0072] Figure 3 shows an example of the structure of an organic thin-film solar cell. It is formed of a transparent conductive (ITO) film 9, a hole transport layer 10 such as PEDOT:PSS, an organic semiconductor active layer 11, an electron transport layer 12 such as LiF or an n-type semiconductor, and an electrode 13 made of the silver paste of the present invention.
[0073] Figure 4 shows an example of the structure of a photosensitized solar cell. Between the upper and lower 14 transparent conductive (ITO) films, 19 platinum layer, 18 electrolyte, 17 dyed titanium oxide are sealed with 16 spacers, and the silver paste of the present invention is used as a current collector 15 to obtain electricity.
[0074] 5 shows an example of the configuration of a contactless ID. An IC chip 23 is bonded to a conductive antenna 22 patterned on a substrate 24 using the silver paste of the present invention, and a protective film 20 is attached using an adhesive 21. Here, the IC chip is used to store, accumulate, and calculate data. Contactless ID is an RFID (Radio Frequency Identification), contactless IC card, contactless IC tag, data carrier (recording medium), or wireless card that uses radio waves to identify individuals and transmit data between a reader or reader / writer. Its applications include, for example, ID management and history management in toll collection systems, location management in road usage status management systems, and cargo and parcel tracking and management systems. EXAMPLES
[0075] The present invention will now be described in detail with reference to examples, but the present invention is not limited to these examples. In the examples, "parts" means parts by mass, and "%" means % by mass.
[0076] <Weight average molecular weight> The weight average molecular weight was measured using a Shodex GPC-104 / 101 system manufactured by Showa Denko KK Column: Shodex KF-805L, KF-803L, KF-802 Detector: Differential Refractometer (RI) Column temperature: 40℃ Eluent: Tetrahydrofuran (THF) Flow rate: 1.0 mL / min Sample concentration: 0.2% Standard sample for calibration curve: TSK standard polystyrene
[0077] <Particle thickness and aspect ratio> The average long diameter of 30 particles was directly observed with a scanning electron microscope, and a sample was prepared by solidifying the fine particles with a commercially available epoxy resin. The cross section of the sample was directly observed with a scanning electron microscope (magnification 2000 times), and the average thickness of 30 fine particles within the field of view was obtained and the average aspect ratio was calculated. The scanning electron microscope used was a TM-1000 manufactured by Hitachi High-Technologies Corporation.
[0078] [Flake-shaped conductive fine particle manufacturing example 1] 700 parts of pure water were added to 340 parts of silver nitrate (special reagent grade), followed by 700 parts of 25% ammonia water to prepare a silver complex aqueous solution. Meanwhile, a reducing aqueous solution was prepared by mixing 111 parts of hydroquinone (special reagent grade), anhydrous potassium sulfite (special reagent grade), and 1260 parts of pure water. The reducing aqueous solution was placed in a beaker, and the silver complex aqueous solution was added while vigorously stirring. During the reaction, the temperature of the mixture was kept constant at 25°C. After the addition was completed, the mixture was thoroughly stirred to complete the reduction and precipitation, and the precipitated silver powder was filtered and separated, washed with water, and dried to obtain reduced silver powder. 98 parts of reduced silver powder was mixed with 2 parts of oleic acid, and rotated in a ball mill together with zirconia balls with a diameter of 2 mm for 30 minutes to flatten the mixture, obtaining silver powder A. Silver powder A had a thickness of 1.2 μm and an aspect ratio of 10.
[0079] [Amine-modified polyfunctional oligomer synthesis example 1] A 2-liter flask equipped with a reflux condenser was charged with 893 parts of trimethylolpropane PO (propylene oxide) modified triacrylate (Aronix M321: TMPPOAc, manufactured by Toa Gosei Co., Ltd.) and 61 parts of ethanolamine (monoethanolamine: MEA, manufactured by Nippon Shokubai Co., Ltd.), and the mixture was reacted at normal pressure at 50°C for 3 hours with stirring to obtain an amine-modified polyfunctional oligomer 1. The amine-modified polyfunctional oligomer 1 has a tertiary amino group, one hydroxyl group, a weight average molecular weight of 1,000, and four functional groups. [Amine-modified polyfunctional oligomer synthesis example 2] Into a flask equipped with a reflux condenser, 592 parts of trimethylolpropane triacrylate (TMPAc: Aronix M309 manufactured by Toagosei Co., Ltd.) and 61 parts of ethanolamine were added, and the mixture was reacted at 50° C. under normal pressure with stirring for 3 hours to obtain an amine-modified polyfunctional oligomer 2. The amine-modified polyfunctional oligomer 2 has a tertiary amino group, a weight-average molecular weight of 700, and four functional groups.
[0080] Example 1 15 parts of amine-modified polyfunctional oligomer 1, 65 parts of isobornyl acrylate (IBXA, Osaka Organic Chemical Industry Co., Ltd.), 25 parts of epoxy acrylate (Ebecryl 600, Daicel-Allnex Co., Ltd.), 10.5 parts of Irgacure 379 (BASF Co., Ltd.) as a polymerization initiator, and 0.5 parts of N-nitrosophenylhydroxyamine aluminum salt (Q-1301, Wako Pure Chemical Industries, Ltd.) as a polymerization inhibitor were mixed with a dissolver and stirred until completely dissolved. Then, 884 parts of silver powder A was added, stirred with a dissolver for 15 minutes, and thoroughly kneaded with a three-roll mill to obtain active energy ray curable conductive paste 1.
[0081] [Examples 2 to 6] Active energy ray-curable conductive pastes 2 to 13 were obtained in the same manner as in Example 1, except that the raw materials and compounds shown in Table 1 were used. The abbreviations in the table stand for the following. <Monofunctional (meth)acrylate having an alicyclic hydrocarbon group (B)> FA-511AS: Dicyclopentenyl acrylate (manufactured by Resonac) FA-512AS: Dicyclopentenyloxyethyl acrylate (manufactured by Resonac) FA-513AS: Dicyclopentanyl acrylate (manufactured by Resonac) <Monomer (C)> Ebecryl 600: Bisphenol A type epoxy acrylate (manufactured by Daicel Allnex) NK Ester A-DCP: Tricyclodecane dimethylol dicaprolactonate diacrylate (manufactured by Shin-Nakamura Chemical Co., Ltd.) DTMPTAc: Ditrimethylolpropanetetraacrylate (manufactured by Toagosei Co., Ltd.) <Other monomers> Aronix M-101: Phenol EO modified acrylate (manufactured by Toagosei Co., Ltd.) ACMO: Acryloylmorpholine (KJ Chemicals) <Conductive particles> Silver powder B (commercially available flake-shaped silver particles, average particle size 3 μm, thickness 3 μm, aspect ratio 5) Silver powder C (commercially available foil-shaped silver particles, average particle size 6 μm, thickness 0.1 μm, aspect ratio 60)
[0082] [Comparative Examples 1 to 6] Active energy ray-curable conductive pastes 14 to 19 were obtained in the same manner as in Example 1, except that the raw materials and compounds shown in Table 1 were used. The abbreviations in the table are as described above.
[0083] The active energy ray-curable conductive pastes 1 to 19 obtained in the above Examples 1 to 13 and Comparative Examples 1 to 6 were subjected to the following characteristic measurements and their physical properties were evaluated.
[0084] (1) Liquidity assessment The viscosity of the obtained active energy ray curable conductive paste was measured at 2, 5, and 20 rotations of the rotor in a 25°C environment using an E-type viscometer TV250H (manufactured by Toki Sangyo Co., Ltd.) and rotor No. 3. The fluidity was evaluated. The viscosity and thixotropy index value (TI value) are defined below. The viscosity was measured 2 minutes after the start of rotation. Viscosity: Viscosity measured at 5 revolutions TI value = (viscosity at 2 revolutions) / (viscosity at 20 revolutions)
[0085] <Evaluation criteria (viscosity)> A: Viscosity is less than 30 Pa·s (good) B: Viscosity is 30 Pa·s or more and less than 80 Pa·s (usable) C: Viscosity is 80 Pa·s or more but less than 150 Pa·s (slightly poor) D: Viscosity is 150 Pa·s or more but less than 250 Pa·s (poor) The practical level is rated A or B.
[0086] <Evaluation criteria (TI value)> A: TI value = 1 or more but less than 2 (good) B: TI value = 2 or more and less than 3 (usable) C: TI value = 3 or more but less than 4 (slightly poor) D: TI value = 4 or more (bad) The practical level is rated A or B.
[0087] (2) Measurement of volume resistivity The volume resistivity of the conductive layer was measured to evaluate the conductivity. Conductive ink was printed on a polyester film (Toray "S10S", thickness 100μm) using a stainless steel screen plate (screen mesh 400 lines / inch, linearity 23μm) with a pattern of 50 x 100 mm, and UV was irradiated under one 120w / cm air-cooled metal halide lamp (Ceritec UV irradiation device EUV752C) at a conveyor speed of 3m / min and an accumulated illuminance of 500mJ / cm2. The surface resistance was measured using a 4-depth resistivity meter (Mitsubishi Chemical Analytech Loresta GP), and the film thickness was measured using a film thickness meter (Nikon Digimicro) to calculate the volume resistivity. In the table, "-" indicates that the specimen was not cured and therefore could not be evaluated. <Evaluation criteria> A: Volume resistivity less than 100μΩcm B: Volume resistivity 100μΩcm or more and less than 500μΩcm C: Volume resistivity 500μΩ or more and less than 1000μΩcm D: Volume resistivity 1000μΩ or more The practical level is rated A or B.
[0088] (3) Printability evaluation The obtained active energy ray curable conductive paste was attached to a semi-automatic screen printer SSA-PC660IP (Seria Corporation) with a stainless steel screen plate (400 mesh 400 lines / inch, linearity 23 μm) and printed sheet by sheet on a polyester film (Toray PET film "Lumirror T60", thickness 100 μm) to form a coating layer with a pattern of 50 × 100 mm. A total of 100 sheets were printed, and the 100th print was printed under one 120 w / cm air-cooled metal halide lamp at a conveyor speed of 3 m / min and an accumulated illuminance of 500 mJ / cm. 2 The printed state was evaluated visually after curing with ultraviolet light. <Evaluation criteria> A: No scratches and good smoothness B: No scratches and slightly poor smoothness C: Scratched and slightly poor smoothness D: Many scratches and poor smoothness The practical level is rated A or B.
[0089] (4) Curability evaluation The obtained active energy ray curable conductive paste was printed on a polyester film ("S10S", thickness 100 μm, manufactured by Toray Industries, Inc.) using a stainless steel screen plate (screen mesh 400 lines / inch, linearity 23 μm) to form a coating layer with a pattern of 50 × 100 mm. Next, ultraviolet rays were irradiated at an integrated illuminance of 500 mJ / cm using one 120 w / cm air-cooled metal halide lamp at a conveyor speed of 3 m / min. 2 The cured conductive layer was irradiated with light and the curability was evaluated according to the following criteria. <Evaluation criteria> A: No fingerprints left when touched with a finger (good) B: Fingerprints are slightly left when touched (slightly poor) C: Fingerprints left when touched (defective) The practical level rating is A.
[0090] (5) Adhesion evaluation - 1 The adhesion of the ITO deposition film to the deposition surface was evaluated. An active energy ray-curable conductive paste was printed on an ITO deposition film (Tetlite TCF KH150NM3-50-MR1 / PT125 manufactured by Oike Kogyo Co., Ltd.) that had been annealed at 140°C for 60 minutes, using a stainless steel screen plate (screen mesh 400 lines / inch, linearity 23 μm) with a pattern of 50 × 100 mm. Then, using one 120 w / cm air-cooled metal halide lamp, ultraviolet rays were irradiated at an integrated illuminance of 500 mJ / cm at a conveyor speed of 3 m / min. 2The conductive layer that had been irradiated and cured was cut with a utility knife to make 11 cuts at 1 mm intervals and 11 cuts perpendicular to those cuts so as not to cut the substrate, forming a total of 100 squares, 10 vertical and 10 horizontal. Next, cellophane tape (25 mm wide) manufactured by Nichiban Co., Ltd. was applied onto the squares, and the cellophane tape was quickly peeled off by hand, and the condition of the remaining squares was evaluated according to the following criteria. <Evaluation criteria> A: 85% or more of the area is not peeled off (good) B: The area that has not peeled off is 70% or more but less than 85% (usable). C: The area that has not peeled off is 30% or more but less than 70% (slightly poor) D: Less than 30% of the area is not peeled off (defective) -: Not cured, so evaluation is not possible The practical level is rated A or B.
[0091] (6) Adhesion evaluation - The adhesion to two glass substrates was evaluated. A 50x100mm pattern of active energy ray curable conductive paste was printed on a glass substrate (Eagle XG-28-6) using a stainless steel screen plate (screen mesh 400 lines / inch, linear 23μm), then one 120w / cm air-cooled metal halide lamp was used to irradiate ultraviolet light at an integrated illuminance of 500mJ / cm2 under the condition of a conveyor speed of 3m / min, and the cured conductive layer was cut with a cutter knife to make 11 cuts at 1mm intervals and 11 cuts at right angles to the cuts so as not to cut the substrate, forming a total of 100 squares, 10 squares vertically and 10 squares horizontally. Next, Nichiban cellophane tape (25mm wide) was applied on the squares, and the cellophane tape was quickly peeled off by hand, and the condition of the remaining squares was evaluated according to the following criteria. <Evaluation criteria> A: 85% or more of the area is not peeled off (good) B: The area that has not peeled off is 70% or more but less than 85% (usable). C: The area that has not peeled off is 30% or more but less than 70% (slightly poor) D: Less than 30% of the area is not peeled off (defective) -: Not cured, so evaluation is not possible The practical level is rated A or B.
[0092] As shown in Table 1, in Examples 1 to 13, the TI value was less than 3.0, the fluidity was excellent, the printability was good, the active energy ray curability was good, and a low volume resistance value of the order of 10 μΩcm was obtained. Furthermore, in Examples 1 to 13, all pastes had good adhesion to ITO deposition film and glass.
[0093] In Comparative Example 1, the curability was good, but the adhesion to the ITO vapor-deposited film was poor. In Comparative Examples 2 and 4, in addition to the poor adhesion to the ITO vapor-deposited film, the volume resistivity was high, and the printed matter had some fading and poor printability.
[0094] Comparative Example 3, which used silver powder C, did not cure even when irradiated with ultraviolet light.
[0095] In Comparative Example 5, the adhesion to the ITO deposition film and glass was good, but the volume resistivity was high and the electrical continuity was poor.
[0096] (7) Evaluation of heat cycle resistance of electrical conductivity The polyester film samples laminated with the UV-cured coating film of the conductive ink of Examples 1 to 13 and Comparative Examples 1 to 6 prepared in the measurement of volume resistivity in (2) above were subjected to a heat cycle test of 1,000 cycles (one cycle is 1 hour in the low temperature bath and 1 hour in the high temperature bath) in a thermal shock tester (TSE-11 manufactured by ESPEC Corp.) under conditions of a low temperature bath temperature of -40°C, a high temperature bath temperature of 85°C, and a retention time in each bath of 1 hour, and then the volume resistivity of each sample taken out was measured in the same manner as described in (2) above, and the resistance value variation rate ((volume resistivity after heat cycle - volume resistivity in (2) above) / volume resistivity in (2) above%) was calculated when compared with the measured volume resistivity values in (2) above. A: Fluctuation rate of volume resistivity is less than ±25% B: Fluctuation rate of volume resistivity is ±25% or more and less than ±50% C: Fluctuation rate of volume resistivity is ±50% or more and less than ±90% D: Volume resistivity fluctuation rate is ±90% or more The practical level is rated A or B.
[0097] (8) Heat cycle resistance evaluation of adhesion A heat cycle test of 1000 cycles was carried out on the glass substrate samples laminated with the UV-cured coating of conductive ink obtained in (6) Adhesion evaluation-2 above under the same conditions as in (7) Conductive heat cycle resistance evaluation. The conductive layer of the UV-cured coating of conductive ink of each sample taken out was cut with a utility knife, making 11 cuts at 1 mm intervals and 11 cuts at right angles to the above, forming a total of 100 squares, 10 squares vertically and 10 squares horizontally. Next, cellophane tape (25 mm wide) made by Nichiban Co., Ltd. was applied on top of the squares, and the cellophane tape was quickly peeled off by hand, and the condition of the remaining squares was evaluated according to the following criteria. A: 85% or more of the area is not peeled off (good) B: The area that has not peeled off is 70% or more but less than 85% (usable). C: The area that has not peeled off is 30% or more but less than 70% (slightly poor) D: Less than 30% of the area is not peeled off (defective) -: Not cured, so evaluation is not possible The practical level is rated A or B. [Table 1] [Industrial Applicability]
[0098] According to the present invention, it is possible to impart excellent adhesion to transparent conductive films, such as ITO vapor deposition films, and glass substrates, to which it was previously difficult to impart adhesion to active energy ray-curable conductive pastes, and furthermore, since the paste has low resistance and good printability, it is possible to form various circuits, and since it does not require heating for curing, it is possible to form circuits on substrates with poor heat resistance. Furthermore, since the printed circuits have excellent stability in conductivity and adhesion even against sudden temperature changes, it is suitable for use in applications where the paste is exposed to large temperature changes, which was previously difficult to apply. [Explanation of symbols]
[0099] 1: Insulating layer (protective layer) 2: Signal wiring (silver paste) 3: Base material 4: Cover glass 5: OCA 6a: Silver wiring X (silver paste) 6b: Silver wiring Y (silver paste) 7a: Transparent conductive (ITO) film X 7b: Transparent conductive (ITO) film Y 8: Display 9: Transparent conductive (ITO) film 10: Hole transport layer 11: Organic semiconductor active layer 12:Electron transport layer 13: Electrode (silver paste) 14: Transparent conductive (ITO) film 15: Current collector (silver paste) 16: Spacer 17: Titanium oxide + dye 18: Electrolyte 19: Platinum layer 20: Protective film 21: Adhesive 22: Conductive antenna (silver paste) 23: IC chip 24: Base material
Claims
1. The active energy ray-curable conductive paste contains flake-shaped conductive fine particles having a thickness of 0.5 to 5 μm and an aspect ratio of 1 to 20, an amine-modified polyfunctional oligomer (A), a monofunctional (meth)acrylate having an alicyclic hydrocarbon group (B), and a polymerization initiator, and contains the flake-shaped conductive fine particles in an amount of 50 to 95 mass % based on the total mass of the paste.
2. 2. The active energy ray-curable conductive paste according to claim 1, wherein the monofunctional (meth)acrylate (B) having an alicyclic hydrocarbon group includes a monofunctional (meth)acrylate having a polycyclic alicyclic hydrocarbon group.
3. 2. The active energy ray-curable conductive paste according to claim 1, wherein a mass ratio ((A):(B)) of the amine-modified polyfunctional oligomer (A) to the monofunctional (meth)acrylate having an alicyclic hydrocarbon group (B) is 95:5 to 5:
95.
4. 2. The active energy ray-curable conductive paste according to claim 1, wherein the amine-modified polyfunctional oligomer (A) has a hydroxyl group and a weight average molecular weight of 500 to 2,000.
5. The active energy ray-curable conductive paste according to claim 1, further comprising a monomer (C) having at least one structure selected from a cycloolefin structure, a trimethylolpropane-derived structure, an epoxy-derived structure, a pentaerythritol-derived structure, and a glycerin-derived structure (excluding the oligomer (A) and the monofunctional (meth)acrylate (B)).
6. 2. The active energy ray-curable conductive paste according to claim 1, which is for screen printing.
7. A wiring board having a conductive layer formed from the active energy ray-curable conductive paste according to any one of claims 1 to 6 on a substrate.
8. An electronic device comprising the wiring board according to claim 7.
Citation Information
Patent Citations
Active energy ray curing type conductive ink composition
JP2007119682A